(untitled) (Research, Society and Development, 2025)
Bariatric surgery is one of the main approaches in the treatment of obesity, promoting weight loss and improving quality of life. However, it may lead to nutritional deficiencies due to anatomical and physiological changes in the gastrointestinal tract, which impair nutrient absorption. This study aims to conduct a literature review on nutritional deficiencies in adults undergoing bariatric surgery, with an emphasis on vitamin D, folic acid (B9), cobalamin (B12), and iron. Scientific literature shows that these deficiencies are frequent after the procedure, mainly due to changes in the digestive tract and the imposed dietary restrictions. The analyzed studies address these deficiencies in individuals over 18 years of age. Among the most common deficits, iron deficiency stands out, which can lead to iron-deficiency anemia. Vitamin D deficiency is also recurrent, affecting bone health and calcium absorption. Deficiency in B-complex vitamins, especially B9 and B12, can cause significant neurological changes. Given this scenario, continuous nutritional follow-up is essential, including laboratory evaluation and appropriate supplementation. This approach contributes to the prevention of complications, supports recovery, and improves long-term quality of life. Multidisciplinary care is indispensable for the success of the treatment and the well-being of patients undergoing bariatric surgery.